Perovskite solar cell and preparation method thereof
By adopting the dry carbon electrode film method, the problem of perovskite solar cells being prone to internal short circuit during the preparation process is solved, and efficient photoelectric conversion and low-cost production are achieved.
Patent Information
- Application Number
- CN202411998828.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
Existing perovskite solar cells are prone to internal short circuit problems during the preparation process, resulting in a decrease in photoelectric conversion efficiency.
A dry carbon electrode film is used to make a film by applying a carbon material and a binder to the insulating layer without solvents, and heat to remove the binder to form a blank device with high leakage resistance, thereby preventing the occurrence of internal short circuit.
It effectively prevents battery short circuits, improves photoelectric conversion efficiency, and is simple in process and low in cost, which is suitable for large-scale production.
Smart Images

Figure BDA0005226329570000121 
Figure HDA0005226329670000011 
Figure HDA0005226329670000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have the advantages of high theoretical conversion efficiency and low cost, and have great research and development potential. Mesoporous perovskite solar cells have significant advantages in increasing the contact area between perovskite and charge transport layer (electron transport layer, hole transport layer), increasing carrier separation, and improving the photoelectric conversion efficiency of the battery. The preparation method is to first disperse nano-sized electron transport material, hole transport material, insulating layer and other material particles in a solvent to prepare a slurry, apply it on the surface of a conductive substrate such as FTO glass, heat to remove the solvent to form a porous structure, then drip the perovskite precursor solution and infiltrate it into the pores, and promote the crystallization of perovskite by heating and evaporation to make a mesoporous perovskite solar cell.
[0003] A representative mesoporous perovskite solar cell is a three-layer mesoporous carbon electrode mesoporous perovskite solar cell (see references J.Phys.Chem.Lett.2014,5,17,2927-2934, Nano Lett.2014,14,2,1000–1004, patent CN202210806436.4, etc.). In the preparation process of the cell, the electron transport layer slurry, the insulating layer slurry, and the carbon slurry are first coated on the FTO substrate in sequence, and the pine alcohol in the slurry is heated to remove and the ethyl cellulose is decomposed and volatilized to form pores to form a "blank device", and then the perovskite precursor solution is dripped into the blank device, and the perovskite is heated and evaporated to induce crystallization of the perovskite to make a finished cell. This method does not require expensive hole transport materials such as Spiro-OMeTAD, which greatly reduces the cost. At the same time, the carbon electrode does not absorb halogens and does not react chemically with the perovskite, which greatly improves the stability of the battery device.
[0004] It can be seen that the key to the preparation of mesoporous perovskite solar cells lies in the preparation of high-performance slurry. Perovskite solar cell slurry generally uses pine alcohol as a solvent, ethyl cellulose and organic acid as thickeners and surfactants, respectively, and is made by mixing, rotary evaporation and other processes. In the preparation process of three-layer mesoporous carbon electrode perovskite solar cells, the problem of internal short circuit is often encountered. This is because after the carbon slurry is coated on the insulating layer slurry, due to the strong solubility and permeability of pine alcohol, the carbon slurry is easy to corrode and penetrate the insulating layer, resulting in short circuit leakage of the device. Internal short circuit will greatly increase the leakage loss, resulting in a significant decrease in the photoelectric conversion efficiency of the device. In the previous production process, most of the methods used were to cool and age the insulating layer, and then apply carbon slurry after the insulating layer was solidified to a certain extent. This method can alleviate the corrosion of the carbon slurry to the insulating layer to a certain extent, but it cannot completely prevent the carbon electrode from penetrating through the insulating layer, so it cannot completely solve the short circuit problem. For the production of large-area batteries, the negative impact of the short circuit problem is even more serious. It is necessary to develop a method that can more effectively prevent the carbon electrode from penetrating the insulating layer and contacting the electron transport layer, so as to prevent internal short circuit of the device and improve the efficiency of the device. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is a perovskite solar cell and a preparation method thereof. The perovskite solar cell provided by the present invention has high leakage resistance, no internal short circuit, and high photoelectric conversion efficiency.
[0006] The present invention provides a perovskite solar cell, comprising:
[0007] Conductive substrate;
[0008] An electron transport layer composited on the conductive substrate;
[0009] An insulating layer composited on the electron transport layer;
[0010] A carbon electrode composited on the insulating layer;
[0011] The electron transport layer is prepared from an electron transport layer slurry; the electron transport layer slurry is prepared from raw materials including terpineol, a dispersant, a thickener, ethanol and an electron transport material;
[0012] The insulating layer is prepared from an insulating layer slurry; the insulating layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an insulating layer material;
[0013] The carbon electrode is prepared by heating a dry carbon electrode film to remove a binder; the dry carbon electrode film is prepared by carbon slurry; the carbon slurry is prepared by raw materials including water, a binder and a carbon material.
[0014] Preferably, the dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol;
[0015] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL;
[0016] The volume of the ethanol is 1 to 3 times the volume of terpineol.
[0017] Preferably, the electron transport material comprises TiO2, SnO2 or ZnO;
[0018] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm;
[0019] In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.
[0020] Preferably, the method for preparing the electron transport layer slurry comprises the following steps:
[0021] Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry;
[0022] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
[0023] Preferably, the insulating layer material includes ZrO2, Al2O3 or SiO2;
[0024] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm;
[0025] In the raw materials for preparing the insulating layer slurry, the mass ratio of the insulating layer material to the amount of the pinene alcohol is 150-450 mg:1 mL.
[0026] Preferably, the method for preparing the insulating layer slurry comprises the following steps:
[0027] Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry;
[0028] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
[0029] Preferably, the carbon material is selected from graphite and conductive carbon black;
[0030] The mass of the carbon material is 15% to 50% of the mass of water;
[0031] The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the mass of the binder is 0.5% to 5% of the mass of water;
[0032] The thickness of the dry carbon electrode film is 10-100 μm.
[0033] The present invention also provides a method for preparing the perovskite solar cell described above, comprising the following steps:
[0034] A) coating an electron transport layer slurry on a conductive substrate and heating to form an electron transport layer; then coating an insulating layer slurry on the electron transport layer and heat-keeping to obtain a semi-finished device;
[0035] B) attaching a dry carbon electrode film to the insulating layer in the semi-finished device, heating to remove the binder in the dry carbon electrode film, and obtaining a blank device without perovskite;
[0036] C) dropping a perovskite precursor solution onto the bottom electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;
[0037] D) Covering the bottom electrode of the device obtained in step C) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
[0038] Preferably, in step A), the coating thickness of the electron transport layer slurry is 0.5 to 2 μm;
[0039] The coating thickness of the insulating layer slurry is 1 to 3 μm;
[0040] In step B), the pressure of the attachment is 0.1-10 kg / m 2 .
[0041] Preferably, in step C), in the perovskite precursor solution, the solvent includes at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of;
[0042] The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L;
[0043] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ;
[0044] The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.
[0045] The key reason why the carbon electrode corrodes the insulating layer is that the carbon slurry contains highly soluble solvents such as pine alcohol. If such highly soluble solvents are not used in the preparation process of the carbon electrode, it is possible to eliminate the corrosion problem of the insulating layer. The present invention first makes the carbon material and the binder into a film, and then directly attaches the film to the device, so that the coating can be achieved without the help of a solvent. Therefore, the present invention adopts a dry coating strategy, first prepares a carbon electrode film that does not contain a solvent, and then attaches the film to the insulating layer, heats to remove the binder, and a blank device with high leakage resistance can be formed, and further a perovskite solar cell without internal short circuit is prepared, and the photoelectric conversion efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 A comparison diagram of the coating method of the present invention and the conventional perovskite solar cell;
[0047] Figure 2 This is a comparison diagram of the step 6) of Example 1 and Example 2 of the present invention before and after the dry carbon electrode film is attached to the insulating layer in the semi-finished device by rolling with a glass rod;
[0048] Figure 3 IV test curves of the mesoporous perovskite solar cells obtained in Examples 1-2 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The present invention provides a perovskite solar cell, comprising:
[0051] Conductive substrate;
[0052] An electron transport layer composited on the conductive substrate;
[0053] An insulating layer composited on the electron transport layer;
[0054] A carbon electrode composited on the insulating layer;
[0055] The electron transport layer is prepared from an electron transport layer slurry; the raw materials for preparing the electron transport layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an electron transport material;
[0056] The insulating layer is prepared from an insulating layer slurry; the raw materials for preparing the insulating layer slurry are composed of pine alcohol, a dispersant, a thickener, ethanol and an insulating layer material;
[0057] The carbon electrode is made of a dry carbon electrode film by heating to remove the binder; the dry carbon electrode film is made of carbon slurry; the raw materials for preparing the carbon slurry consist of water, a binder and a carbon material.
[0058] About conductive substrate:
[0059] The conductive substrate includes FTO glass, ITO glass or any other transparent conductive substrate, preferably FTO glass. The film thickness of the conductive substrate is 200-500nm, preferably 350nm.
[0060] About the electron transport layer:
[0061] The electron transport material includes TiO2, SnO2, ZnO or any other n-type semiconductor material.
[0062] The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.
[0063] The usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL, preferably 100 mg:1 mL.
[0064] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.
[0065] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; specifically, ethyl cellulose and polyvinyl alcohol; the average molecular weight of the thickener is 5000-20000, preferably 10000; the usage ratio of the thickener to the pine oil is 50-250 mg:1 mL, preferably 150 mg:1 mL.
[0066] The volume of the ethanol is 1 to 3 times, preferably 2 times, the volume of terpineol.
[0067] The method for preparing the electron transport layer slurry comprises the following steps:
[0068] The pine alcohol, dispersant, thickener, ethanol and electron transport material are mixed, and the ethanol is removed by rotary evaporation to obtain an electron transport layer slurry.
[0069] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0070] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 40 to 60° C., preferably 45° C.; and a time of 4 to 12 h, preferably 6 h.
[0071] About the insulation layer:
[0072] The insulating layer material includes ZrO2, Al2O3, SiO2 or any other insulating material.
[0073] The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; preferably, the particle size is 30 to 50 nm.
[0074] The usage ratio of the insulating layer material to the pine alcohol is 150-450 mg:1 mL, for example, 250 mg:1 mL.
[0075] The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; specifically, acetylacetone, lauric acid and acetic acid, with a volume ratio of 1:1:2; the volume of the dispersant is 1% to 10% of the volume of terpineol, preferably 4%.
[0076] The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; specifically, ethyl cellulose and polyvinyl alcohol; the average molecular weight of the polyvinyl alcohol is 5000-20000, preferably 10000; the dosage ratio of the thickener to the pine oil is 50-250 mg:1 mL, preferably 150 mg:1 mL.
[0077] The volume of the ethanol is 1 to 3 times, preferably 2 times, the volume of terpineol.
[0078] The method for preparing the insulating layer slurry comprises the following steps:
[0079] The pine alcohol, dispersant, thickener, ethanol and insulating layer material are mixed, and the ethanol is removed by rotary evaporation to obtain insulating layer slurry.
[0080] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0081] The rotary evaporation adopts a rotation speed of 15 to 60 rpm, preferably 30 rpm; an air pressure of 15 to 50 mbar, preferably 20 mbar; a heating temperature of 40 to 60° C., preferably 45° C.; and a time of 4 to 12 h, preferably 6 h.
[0082] About Carbon Electrode:
[0083] The carbon material is selected from graphite and conductive carbon black; preferably, graphite with a particle size of 5 to 10 μm (preferably 7 μm) and conductive carbon black with a particle size of 20 to 50 nm (preferably 30 nm) are used in a mass ratio of 4:1.
[0084] The mass ratio of the carbon material to water is 150-600 mg:1 mL, preferably 500 mg:1 mL.
[0085] The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the average molecular weight of the binder is 5000-20000, preferably 10000; the mass ratio of the binder to water is 5-50 mg:1 mL, preferably 20 mg:1 mL.
[0086] The preparation method of the carbon slurry comprises the following steps:
[0087] Water, a binder and a carbon material are mixed to obtain a carbon slurry.
[0088] The mixing is at least one of mechanical stirring, ball milling, sand milling, ultrasonic mixing and high shear emulsification; and the mixing time is ≥12h.
[0089] The dry carbon electrode film does not contain a solvent. The dry carbon electrode film is made by removing water from the carbon slurry. The water removal method can be drying.
[0090] Specifically, the method of preparing the carbon slurry into a dry carbon electrode film includes:
[0091] The carbon slurry is made into a film, and the water is dried to form a dry carbon electrode film.
[0092] The method of making the carbon slurry into a film is selected from slit coating, wire rod coating, screen printing, roller pressing, or any other method of preparing a slurry film.
[0093] The method for drying the water is selected from a heating drying method (temperature is 60-120° C., preferably 100° C.), a blast drying method, a vacuum drying method, or any other method suitable for drying water.
[0094] The thickness of the dry carbon electrode film is 10-100 μm, such as 40 μm or 80 μm.
[0095] The present invention also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:
[0096] A) coating an electron transport layer slurry on a conductive substrate and heating to form an electron transport layer; then coating an insulating layer slurry on the electron transport layer and heat-keeping to obtain a semi-finished device;
[0097] B) attaching a dry carbon electrode film to the insulating layer in the semi-finished device, heating to remove the binder in the dry carbon electrode film, and obtaining a blank device without perovskite;
[0098] C) dropping a perovskite precursor solution onto the bottom electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device;
[0099] D) Covering the bottom electrode of the device obtained in step C) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
[0100] In step A):
[0101] The coating thickness of the electron transport layer slurry is 0.5-2 μm, preferably 0.8 μm.
[0102] The coating thickness of the insulating layer slurry is 1-3 μm, preferably 1.5 μm.
[0103] The coating method is slit coating, wire rod coating, screen printing or any other slurry coating method.
[0104] The heating temperature is 400-600° C., preferably 500° C.; the heating time is 15-60 min, preferably 40 min.
[0105] The insulation temperature is 400-600° C., preferably 500° C.; the insulation time is 15-60 minutes, preferably 40 minutes.
[0106] In step B):
[0107] The attachment method is selected from a pressing method, a rolling method or any other method used for dry electrode attachment, and the attachment pressure is 0.1 to 10 kg / m 2 , preferably 0.5kg / m 2 .
[0108] The heating temperature is 300-500° C., preferably 400° C.; the heating time is 15-60 min, preferably 40 min.
[0109] In step C):
[0110] In the perovskite precursor solution, the solvent includes at least one of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO); the solute is ABX3 (wherein A is at least one of methylamine (MA) ion, formamidine (FA) ion and cesium (Cs) ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of the following), such as MA 0.4 FA 0.6 In certain embodiments, the solvent comprises DMF and DMSO in a volume ratio of 4:1.
[0111] The concentration of the perovskite precursor solution is 1.0-1.5 mol / L, preferably 1.2 mol / L.
[0112] The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 , preferably 3 μL / cm 2 .
[0113] The annealing temperature is 60-120°C, and the time is 4-24h; preferably, when the annealing temperature is 60°C / 80°C / 100°C / 120°C, the corresponding time is 24h / 16h / 8h / 4h. The annealing is used to remove the solvent in the perovskite precursor solution and precipitate the perovskite.
[0114] In step D):
[0115] The back panel is made of glass, organic glass or other airtight panels.
[0116] The present invention has no particular limitation on the method of connecting the wires, and any method of connecting the wires well known to those skilled in the art may be used.
[0117] The sealant can be commercial sealant, and common ingredients include epoxy resin or ethylene-vinyl acetate copolymer.
[0118] Figure 1 : is a comparison diagram of the coating method of the present invention and the conventional perovskite solar cell. Figure 1 It can be seen that the traditional coating process is to coat the carbon electrode slurry on the ZrO2 insulating layer, which will cause the carbon slurry to dissolve and penetrate the ZrO2 insulating layer, resulting in device short circuit and reduced efficiency; the core point of the method adopted by the present invention is to use dry carbon electrodes. The carbon electrodes will not dissolve or corrode the ZrO2 insulating layer when attached, preventing device short circuit, thereby improving device efficiency.
[0119] Beneficial effects:
[0120] 1) Can effectively prevent battery short circuit: Since the carbon electrode in the present invention is prepared by dry coating, the dry carbon electrode does not contain solvent and will not corrode the insulating layer, thus preventing the device from short circuiting.
[0121] 2) Simple process: low equipment cost, mild production process, low risk and easy operation.
[0122] 3) Low cost: The main raw materials used, such as water, polyvinyl alcohol, carboxymethyl cellulose, etc., are all commonly used and cheap raw materials. No high-priced raw materials or equipment are required, thus reducing costs.
[0123] 4) High device performance: Since the device obtained by this method will not have an internal short circuit, the leakage loss is reduced, thereby ensuring the photoelectric conversion efficiency of the solar cell.
[0124] 5) It is conducive to large-scale production: large-area perovskite solar cells are more sensitive to short-circuit problems. The present invention greatly reduces the risk of short circuits in the battery, which is conducive to the manufacture of large-area perovskite solar cells.
[0125] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0126] In order to further illustrate the present invention, a perovskite solar cell and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the protection scope of the present invention.
[0127] Example 1
[0128] 1) Preparation of electron transport layer slurry:
[0129] Use 20 mL of pineol, 40 mL of ethanol, 0.2 mL, 0.4 mL, 0.2 mL of acetylacetone, acetic acid and lauric acid respectively, 2 g, 1 g of ethyl cellulose (average molecular weight 10,000) and polyvinyl alcohol (average molecular weight 10,000), 2 g of TiO2 with a particle size of 30-50 nm, and perform high shear emulsification for 1 h (speed 6,000 rpm), ball milling for 24 h (speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) to remove ethanol to obtain an electron transport layer slurry.
[0130] 2) Preparation of insulation layer slurry:
[0131] Use 20mL of pineol, 40mL of ethanol, 0.2mL, 0.4mL, 0.2mL of acetylacetone, acetic acid and lauric acid respectively, 2g and 1g of ethyl cellulose (average molecular weight 10000) and polyvinyl alcohol (average molecular weight 10000) respectively, 5g of ZrO2 with a particle size of 30-50nm, and perform high shear emulsification for 1h (speed 6000rpm), ball milling for 24h (speed 300rpm), ultrasound for 1h, and rotary evaporation at 45℃ for 6h (pressure 20mbar) to remove ethanol to obtain an insulating layer slurry.
[0132] 3) Preparation of carbon slurry:
[0133] Use 30 mL of water, 0.6 g of polyvinyl alcohol (average molecular weight 10,000), 0.6 g of carboxymethyl cellulose, 12 g of 7 μm graphite and 3 g of 30 nm conductive carbon black, and perform high shear emulsification for 1 h (rotation speed 6,000 rpm), ball milling for 24 h (rotation speed 300 rpm), and ultrasound for 1 h to make a carbon slurry.
[0134] 4) The carbon slurry was coated on the glass surface by slit coating to form a 40 μm thick film, and after being blown dried in an oven at 100° C., it was peeled off from the glass to obtain a dry carbon electrode film.
[0135] 5) coating the electron transport layer slurry on the conductive substrate with a coating thickness of 0.8 μm, and heating at 500° C. for 40 min to form an electron transport layer; then coating the insulating layer slurry on the electron transport layer with a coating thickness of 1500 nm (1.5 μm), and keeping at 500° C. for 40 min to obtain a semi-finished device.
[0136] 6) A dry carbon electrode film is attached to the insulating layer in the semi-finished device by glass rod rolling, and the dry carbon electrode film is heated at 400° C. for 40 minutes to remove the binder in the dry carbon electrode film, thereby obtaining a blank device without perovskite.
[0137] 7) The perovskite precursor solution (solvent includes DMF and DMSO, volume ratio is 4:1; solute is MA 0.4 FA 0.6 PbI3, concentration of 1.2 mol / L) was added dropwise onto the bottom electrode of the blank device (addition volume was 3 μL / cm 2 ), after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing is performed at 80°C for 16h to obtain a perovskite-containing device.
[0138] 8) A back plate is added to the bottom electrode of the device obtained in step 7), wires are connected, and a sealant is applied to obtain a mesoporous perovskite solar cell.
[0139] Example 2
[0140] The difference from Example 1 is:
[0141] In step 3), 0.6 g of polyvinyl alcohol (average molecular weight 10,000) and 0.6 g of carboxymethyl cellulose were replaced with 1.2 g of hydroxyethyl cellulose;
[0142] In step 4), the carbon slurry is coated on the glass surface into a film with a thickness of 80 μm using a wire rod coating, and after drying in a vacuum drying oven at 100° C., it is peeled off from the glass to obtain a dry carbon electrode film.
[0143] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.
[0144] Figure 2 This is a comparison diagram of the step 6) of Example 1 and Example 2 of the present invention before and after the dry carbon electrode film is attached to the insulating layer in the semi-finished device by glass rod rolling. Among them, Figure 2 1a and 2a are pictures of Example 1 and Example 2 after the dry carbon electrode film is attached by glass rod rolling; Figure 2 1b and 2b in the figure are pictures of Example 1 and Example 2 respectively when the carbon electrode film is attached but not rolled with a glass rod. Figure 2 It can be seen that glass rod rolling can increase the adhesion effect of the carbon electrode on the surface of the insulating layer and reduce the warping of the carbon electrode film.
[0145] Comparative Example 1
[0146] The difference from Example 1 is:
[0147] Step 3): Preparation of carbon slurry:
[0148] Use 20 mL of pine alcohol, 40 mL of ethanol, 0.2 mL of acetylacetone, 0.4 mL of acetic acid and 0.2 mL of lauric acid respectively, 2 g of ethyl cellulose (average molecular weight 10000) and 1 g of polyvinyl alcohol (average molecular weight 10000), 12 g of 7 μm graphite and 3 g of 30 nm carbon black respectively, and carry out high shear emulsification for 1 h (rotation speed 6000 rpm), ball milling for 24 h (rotation speed 300 rpm), ultrasound for 1 h, and rotary evaporation at 45 ° C for 6 h (pressure 20 mbar) in sequence to obtain a carbon slurry.
[0149] Delete step 4).
[0150] In step 6), the carbon slurry is coated on the surface of the insulating layer in the semi-finished device by slit coating with a film thickness of 40 μm, dried at 100° C., and heated at 400° C. for 40 minutes to remove the solvent and binder, thereby obtaining a blank device without perovskite.
[0151] The other steps are the same as those in Example 1 to obtain a mesoporous perovskite solar cell.
[0152] Comparative Example 2
[0153] The difference from Comparative Example 1 is:
[0154] In step 6), the carbon slurry is coated on the surface of the insulating layer in the semi-finished device by slit coating with a film thickness of 80 μm, dried in a vacuum drying oven at 100° C., and heated at 400° C. for 40 minutes to remove the solvent and binder to obtain a blank device without perovskite.
[0155] The other steps are the same as those in Comparative Example 1 to obtain a mesoporous perovskite solar cell.
[0156] Figure 3 The IV test curves of the mesoporous perovskite solar cells obtained in Examples 1-2 and Comparative Examples 1-2 of the present invention are shown in Figure 1. The IV test uses a steady-state solar light source, the test scan range is 1V to 0V, and a reverse scan is used with a scan rate of 50mV / s. Figure 3 It can be seen that the voltage and current of the device prepared by dry coating are significantly improved.
[0157] The electrical properties of the mesoporous perovskite solar cells obtained in Examples 1 to 2 of the present invention and Comparative Examples 1 to 2 were tested, and the results are shown in Table 1. The test conditions are the same as Figure 3 .
[0158] Table 1 Electrical performance test results of mesoporous perovskite solar cells obtained in Examples 1-2 and Comparative Examples 1-2
[0159]
[0160] It can be seen from Table 1 that after the dry coating of the present invention is adopted, the leakage resistance of the device is greatly increased, the leakage loss of the device is suppressed, thereby improving the voltage and current of the device, and finally the photoelectric conversion efficiency of the device is improved by about 6 percentage points.
[0161] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A perovskite solar cell, comprising: Conductive substrate; An electron transport layer composited on the conductive substrate; An insulating layer composited on the electron transport layer; A carbon electrode composited on the insulating layer; The electron transport layer is prepared from an electron transport layer slurry; the electron transport layer slurry is prepared from raw materials including terpineol, a dispersant, a thickener, ethanol and an electron transport material; The insulating layer is prepared from an insulating layer slurry; the insulating layer slurry is prepared from raw materials including pinene alcohol, a dispersant, a thickener, ethanol and an insulating layer material; The carbon electrode is prepared by heating a dry carbon electrode film to remove a binder; the dry carbon electrode film is prepared by carbon slurry; the carbon slurry is prepared by raw materials including water, a binder and a carbon material.
2. The perovskite solar cell according to claim 1, characterized in that The dispersant is selected from at least one of acetylacetone, lauric acid and acetic acid; the volume of the dispersant is 1% to 10% of the volume of terpineol; The thickener is selected from at least one of ethyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; the dosage ratio of the thickener to the terpineol is 50-250 mg: 1 mL; The volume of the ethanol is 1 to 3 times the volume of terpineol.
3. The perovskite solar cell according to claim 1, characterized in that The electron transport material includes TiO2, SnO2 or ZnO; The electron transport material is a nanoparticle with a particle size of 10 to 100 nm; In the raw materials for preparing the electron transport layer slurry, the usage ratio of the electron transport material to the pinene alcohol is 50-200 mg:1 mL.
4. The perovskite solar cell according to claim 1, characterized in that: The method for preparing the electron transport layer slurry comprises the following steps: Mixing pinene alcohol, a dispersant, a thickener, ethanol and an electron transport material, and removing the ethanol by rotary evaporation to obtain an electron transport layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
5. The perovskite solar cell according to claim 1, characterized in that: The insulating layer material includes ZrO2, Al2O3 or SiO2; The insulating layer material is nanoparticles with a particle size of 10 to 100 nm; In the raw materials for preparing the insulating layer slurry, the mass ratio of the insulating layer material to the amount of the pinene alcohol is 150-450 mg:1 mL.
6. The perovskite solar cell according to claim 1, characterized in that: The method for preparing the insulating layer slurry comprises the following steps: Mixing pineol, a dispersant, a thickener, ethanol and an insulating layer material, and removing the ethanol by rotary evaporation to obtain an insulating layer slurry; The rotary evaporation adopts a rotation speed of 15 to 60 rpm, an air pressure of 15 to 50 mbar, a heating temperature of 40 to 60° C., and a heating time of 4 to 12 hours.
7. The perovskite solar cell according to claim 1, characterized in that: The carbon material is selected from graphite and conductive carbon black; The mass of the carbon material is 15% to 50% of the mass of water; The binder is selected from at least one of polyvinyl alcohol, carboxymethyl cellulose and hydroxyethyl cellulose; the mass of the binder is 0.5% to 5% of the mass of water; The thickness of the dry carbon electrode film is 10-100 μm.
8. A method for preparing a perovskite solar cell according to any one of claims 1 to 7, comprising the following steps: A) coating an electron transport layer slurry on a conductive substrate and heating to form an electron transport layer; Then, the insulating layer slurry is coated on the electron transport layer, and after heat preservation, a semi-finished device is obtained; B) attaching a dry carbon electrode film to the insulating layer in the semi-finished device, heating to remove the binder in the dry carbon electrode film, and obtaining a blank device without perovskite; C) dropping a perovskite precursor solution onto the bottom electrode of the blank device, and after the perovskite precursor solution fully penetrates into the carbon electrode, the insulating layer and the electron transport layer, annealing to obtain a perovskite-containing device; D) Covering the bottom electrode of the device obtained in step C) with a back plate, connecting wires, and applying sealant to obtain a mesoporous perovskite solar cell.
9. The preparation method according to claim 8, characterized in that: In step A), the coating thickness of the electron transport layer slurry is 0.5 to 2 μm; The coating thickness of the insulating layer slurry is 1 to 3 μm; In step B), the pressure of the attachment is 0.1-10 kg / m 2 .
10. The preparation method according to claim 8, characterized in that: In step C), the perovskite precursor solution comprises a solvent including at least one of dimethylformamide and dimethyl sulfoxide; the solute is ABX3; wherein A is at least one of methylamine ion, formamidine ion and cesium ion, and B is Pb 2+ and Sn 2+ At least one of, X is 1 - Br - and Cl - At least one of; The concentration of the perovskite precursor solution is 1.0 to 1.5 mol / L; The amount of the perovskite precursor solution added to the blank device is 2-4 μL / cm 2 ; The annealing temperature is 60-120° C. and the annealing time is 4-24 hours.
Citation Information
Patent Citations
Perovskite solar cell and carbon slurry and preparation method thereof
CN115064301A